2022
DOI: 10.1200/op.22.00427
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists' Perspectives on Individualizing Dose Selection for Patients With Metastatic Cancer

Abstract: PURPOSE: Treatment goals for patients with metastatic cancer include prolongation and maintenance of quality of life. Patients and oncologists have questioned the current paradigm of initial dose selection for systemic therapy; however, data on oncologists' dose selection strategies and beliefs are lacking. METHODS: We conducted an electronic international survey of medical oncologists who treat patients with breast and/or gastrointestinal cancers. Survey questions addressed experiences with, and attitudes tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…An American Society of Clinical Oncology (ASCO) survey published in 2022 found that 41% of oncologists who treat breast and/or gastrointestinal cancer patients with capecitabine regularly prescribed it at a starting dose level lower than 1250 mg/m 2 . 26 Based on available data, in December 2022, there was a major update to the label of capecitabine which included new indications and also the addition of 1000 mg/m 2 (twice daily) as starting dose for patients with metastatic breast cancer. 27 While there was an abundance of data to support lower dosing for capecitabine, other oncology drugs that have been approved more recently and have been prescribed to a narrower patient population may not have the necessary data available.…”
Section: Changing the Paradigmmentioning
confidence: 99%
“…An American Society of Clinical Oncology (ASCO) survey published in 2022 found that 41% of oncologists who treat breast and/or gastrointestinal cancer patients with capecitabine regularly prescribed it at a starting dose level lower than 1250 mg/m 2 . 26 Based on available data, in December 2022, there was a major update to the label of capecitabine which included new indications and also the addition of 1000 mg/m 2 (twice daily) as starting dose for patients with metastatic breast cancer. 27 While there was an abundance of data to support lower dosing for capecitabine, other oncology drugs that have been approved more recently and have been prescribed to a narrower patient population may not have the necessary data available.…”
Section: Changing the Paradigmmentioning
confidence: 99%
“…Younger generations of oncologists are increasingly willing to empirically use lower doses of drug in an effort to preserve quality of life, even when that might entail a tradeoff in efficacy. 80 Oncologists are increasingly willing to enroll patients in trials that seek lower toxicity, cost, and patient burden. 81 Oncologists are willing to discuss flexible approaches to dosing that may better balance toxicity and efficacy, particularly in metastatic disease.…”
Section: Financial and Reporting Considerationsmentioning
confidence: 99%
“…To avoid toxicity, more than half of the oncologists prescribe initiation doses that are lower than MTD at least 10% of the time. 3 Alternative strategies include adaptive dose modulations based on evolutionary-based modelling. 4,5 CURATE.AI is an indication-agnostic, AI-derived platform that utilizes a patient's own, prospectivelycalibrated small dataset to create an N-of-1 pro le -analogous to a digital twin -that dynamically personalizes only that patient's dose recommendations.…”
Section: Introductionmentioning
confidence: 99%